Floral biology and pollinator captivating semiochemicals in Goniothalamus wynaadensis (Bedd.) Bedd. (Annonaceae) an endemic tree species of the Western Ghats - Anjali, Jayan; Sreekala, A. K (Plant Science Today, 2023)
Goniothalamus wynaadensis (Bedd.) Bedd. (Family Annonaceae) is an endemic tree species growing in the evergreen forests of the Western Ghats up to 900m asl. The present study aims at understanding the functional floral traits and semiochemicals found in G. wynaadensis which support plant-pollinator interactions. The study revealed G. wynaadensis exhibits abbreviated anthesis (c.28hrs). Goniothalamus flowers exhibit unique features of cantharophily. The study indicated that outcrossing is promoted by protogyny, and pollination efficiency is enhanced by pollen aggregation, anthesis duration, and pollinator trapping which involves a close alignment between petal movements and the circadian rhythm of pollinators. Curculionidae and Nitidulidae beetles are effective pollinators of the plant. In beetle-pollinated flowers, floral scent is a crucial component for pollinator attraction. G. wynaadensis has a strong fruity aroma. The floral scent analysis performed using headspace solid- phase microextraction combined with GC-MS detected various semiochemicals that support plant-pollinator interactions. Ethyl butyrate, isobutyl acetate, 3 hydroxy 3 methyl 2 butanol, isopentyl acetate, and 3 methyl 1 butanol dominate the floral scent of G. wynaadensis.